Deteksi Dini Toleransi Padi Hibrida terhadap Kekeringan menggunakan PEG 6000 - Afa, La Ode; Purwoko, Bambang Sapta; Junaedi, Ahmad; Haridjaja, Oteng; Dewi, Iswari Saraswati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
The objective of this study was to determine a selection method at early stage for drought tolerant hybrid rice. Theexperimental design was split plot with 3 replications. In the first experiment the main plot was concentration of PEG 6000consisting of control and concentration 25% of PEG 6000. The subplots were hybrid genotypes/varieties, i.e. BI485A/BP3,BI485A/BP5, BI485A/BP10, BI485A/BP12, BI485A/BP15, BI599A/BP5, BI599A/BP15, BI665A/BP6, Maro, Hipa 8, IR64and Limboto. In the second experiment the main plot was drought stress level which consisted of control and drought stressat 60% field capacity. The subplots were hybrid genotypes/varieties used in the first experiment. The results showed that PEG 6000 could be used to detect drought tolerant genotypes at early stage. Seedling dry weight was the major character for selecting drought tolerant genotypes. Genotypes BI485A/BP15 and BI559A/BP15 are tolerant to drought and can potentially be grown in rainfed lowland.Keywords: drought tolerant, early selection, hybrid rice, polyethylene glycol